(untitled) (Tempo e Argumento, 2017)
As is common in the History of Present, there is a significant interconnection between politics and academic research regarding the history of the Brazilian military dictatorship. Consequently, it is essential that well-established theoretical formulations guide archival research. This article discusses the alleged revisionism of the historiography on the Brazilian military dictatorship, argues that the recruitment of young left-wing students for the armed struggle has generated a traumatic memory, shows the weakness of the debate about the civil-military character of dictatorship, argues that the institutional framework of the state of exception was still active in 1985 and demonstrates that the military controlled the project of “Abertura”. Keywords: Brazilian Military Dictatorship. Historiography. Revisionism. Memory. Trauma.